KEPEMIMPINAN KEPALA SEKOLAH - Syafrida Syafrida (UNIVERSITAS BENGKULU, 2015)
The purpose of this study is to describe a public elementary school leadership 06 Sindang Kelingi Rejang Lebong district. The method used qualitative descriptive study. Subjects were 06 public elementary school principal sindang Kelingi Rejang Lebong district. Data collection techniques in use is the interview, observation and documentation. The results show that the Elementary School Principal Leadership Negari 06 Sindang Kelingi Rejang Lebong using vision, style, approach, skills, and the role of school leadership.Keywords: principal, leadership